1995
DOI: 10.1126/science.270.5244.1964
|View full text |Cite
|
Sign up to set email alerts
|

Al Coordination Changes in High-Pressure Aluminosilicate Liquids

Abstract: Understanding the effect of pressure on aluminosilicate glass and liquid structure is critical to understanding magma flow at depth. Aluminum coordination has been predicted by mineral phase analysis and molecular dynamic calculations to change with increasing pressure. Nuclear magnetic resonance studies of glasses quenched from high pressure provide clear evidence for an increase in the average coordination of Al with pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
167
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(184 citation statements)
references
References 38 publications
15
167
0
Order By: Relevance
“…It can be observed that the characteristic distance d decreases with density, which suggests a decrease of the medium range order (MRO). On the contrary, the correlation length L does not follow a general behavior with density since it shows a density window between 2.3 and 3.3 g/cm 3 with a maximum at 2.7 g/cm 3 . We notice that the density of the maximum of L corresponds to the density of the beginning of the growth of the Si V fraction (see Fig.…”
Section: First Sharp Diffraction Peakmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be observed that the characteristic distance d decreases with density, which suggests a decrease of the medium range order (MRO). On the contrary, the correlation length L does not follow a general behavior with density since it shows a density window between 2.3 and 3.3 g/cm 3 with a maximum at 2.7 g/cm 3 . We notice that the density of the maximum of L corresponds to the density of the beginning of the growth of the Si V fraction (see Fig.…”
Section: First Sharp Diffraction Peakmentioning
confidence: 99%
“…As a consequence, the model of the network modifier Na atom simply given by stoichiometry (one Na atom involving the appearance of one NBO atom) does not remain valid for ̺ > 3 g/cm 3 . Ultimately, O III are found at high density and their fraction grows up to nearly 50% at ̺ = 5.5 g/cm 3 . Note that 3-fold O atoms (termed triclusters) have already been found both in experiments and in simulations, for example in aluminosilicate glasses 40 .…”
Section: Coordination Numbersmentioning
confidence: 99%
See 2 more Smart Citations
“…N etwork-forming structural motifs such as AO 3 triangular units and AO 4 tetrahedra, where A denotes an electropositive chemical species such as B, Si, or Ge, govern topological ordering in liquid and amorphous oxide materials and therefore have a profound effect on their physical properties (1,2). Examples range from the dependence on network connectivity of the transport properties (e.g., viscosity) of glass-forming and/or magma-related oxide melts (3)(4)(5)(6)(7) to the role played by atomic packing in determining the elastic behavior of glass (8)(9)(10).…”
mentioning
confidence: 99%